2018
DOI: 10.4317/jced.55366
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and validation of the Spanish language version of the questionnaire OQLQ for the assessment of quality of life in orthognathic patients

Abstract: BackgroundOrthognathic surgery is the cornerstone of the treatment of dentofacial deformities, which have a great psychological and social impact on the life of the patient. Patient satisfaction and the impact on quality of life have recently become clinical parameters of growing importance. The aim of this study was to undertake a transcultural adaptation, translation to Spanish and validation of this version of the questionnaire OQLQ, used to measure quality of life in the context of Spanish culture.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…In this study, ICC by dimensions was similar to the value reported by Cunningham et al ( 11 ). The Spanish version ( 13 ), the Brazilian version ( 12 ), the Serbian version ( 14 ), and the Chinese version ( 26 ), including the original scale ( 11 ), have Cronbach's alpha values for all four domains, similar to the results of the OQLQ-TR. The ICCs of the 4 domains of the questionnaire were evaluated based on the homogeneity of the responses to each item.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, ICC by dimensions was similar to the value reported by Cunningham et al ( 11 ). The Spanish version ( 13 ), the Brazilian version ( 12 ), the Serbian version ( 14 ), and the Chinese version ( 26 ), including the original scale ( 11 ), have Cronbach's alpha values for all four domains, similar to the results of the OQLQ-TR. The ICCs of the 4 domains of the questionnaire were evaluated based on the homogeneity of the responses to each item.…”
Section: Discussionmentioning
confidence: 52%
“…Its domains show good evidence for internal reliability (Cronbach a ranging between 0.83 and 0.93) and test-retest reliability (ICC ranging between 0.76 and 0.92) and construct validity in the United Kingdom 13,14 and has been translated in Portuguese, Spanish, Serbian, German, and Japan with the same results. [15][16][17][18][19][20] For the Dutch version of the OQLQ, these measurement properties had to be assessed in a similar way. In this study, the internal and testretest reliability and construct validity have been tested.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The OQLQ has been translated and validated in Portuguese, Spanish, Serbian, German, and Japan but not in the Dutch language. [15][16][17][18][19][20] Although the OQLQ has shown to be a reliable and valid PROM, it is not possible to use it for a Dutch speaking population without careful translation and validation. Presently, there are multiple standardized guidelines for translating questionnaires regarding health-related quality of life; however, there is not enough evidence to favor 1 specific method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jelenleg a kérdőívnek létezik német, portugál, arab, szerb, spanyol, kínai és svéd nyelvre lefordított és validált változata [7][8][9][10][11][12][13]. Magyar nyelven a szájegészséget felmérő kérdőív (OHIP-H -Oral Health Impact Profile) [14] és ennek két rövidített változata [15] érhető el, azonban a dentofacialis eltéréssel élők állapotspecifikus életminőség-vizsgálatát lehetővé tevő, valid és megbízható eszköz mindeddig nem áll rendelkezésünkre.…”
Section: Rövidítésekunclassified